Erosion mitigation in the Waikato District, New Zealand: economic implications for agriculture. (27th December 2016) - Fernandez, Mario Andres; Daigneault, Adam
Abstract: Soil erosion, in its various forms, is caused or aggravated by agricultural activities. Mitigation of surface erosion comprises the construction of shelterbelts, fencing, riparian buffering, and stock reduction. Mitigation of mass‐movement erosion, in turn, takes the form of spaced planting of trees to maintain a persistent, healthy, and complete ground cover. In this article, we assess the economic implications to agriculture of the adoption of mitigation alternatives for erosion control in the Waikato District, New Zealand. The Waikato District presents a spatial pattern of erosion that affects profitability of dairy, and sheep and beef enterprises. We use the Universal Soil Loss Equation and the New Zealand Empirical Erosion Model to estimate erosion figures that are then fed into an economic‐focused, nonlinear, partial equilibrium mathematical programming model of New Zealand land use. Different scenarios are constructed for surface and mass‐movement soil erosion targets ranging from 0% to 50% below baseline levels. We find that achieving surface erosion targets is more expensive than mass‐movement targets, and results in different responses in regional‐level costs, land use, enterprise net revenue, and adoption of mitigation alternatives.